2022
DOI: 10.1155/2022/6448724
|View full text |Cite|
|
Sign up to set email alerts
|

EGR1 Enhances Lymphangiogenesis via SOX18-Mediated Activation of JAK2/STAT3 Pathway

Abstract: Background. Lymphangiogenesis is a process involved in the pathogenesis of many diseases. Identifying key molecules and pathway targeting this process is critical for lymphatic regeneration-associated disorders. EGR1 is a transcription factor, but its function in lymphangiogenesis is not yet known. This study is aimed at exploring the functional activity and molecular mechanism of EGR1 implicated in lymphangiogenesis. Methods. The CCK-8 method, transwell migration assay, and tube formation assay were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, IL-6-mediated JAK–STAT3/VEGF-C signaling pathway can promote tumor growth, invasion and lymphangiogenesis [ 44 ]. Furthermore, a study based on human skin lymphatic endothelial cells (HDLEC) showed that ERG1 can promote lymphangiogenesis by activating the SOX18/JAK/STAT3 cascade [ 45 ]. As a transcription factor that binds to the promoter, EGR1 is considered to be a therapeutic target for many diseases [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, IL-6-mediated JAK–STAT3/VEGF-C signaling pathway can promote tumor growth, invasion and lymphangiogenesis [ 44 ]. Furthermore, a study based on human skin lymphatic endothelial cells (HDLEC) showed that ERG1 can promote lymphangiogenesis by activating the SOX18/JAK/STAT3 cascade [ 45 ]. As a transcription factor that binds to the promoter, EGR1 is considered to be a therapeutic target for many diseases [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%